CALCULATION AND DESIGN OF A PHOTOVOLTAIC PLANT: THE CASE OF THE FACULTY OF ENGINEERING OF THE NATIONAL UNIVERSITY OF LOMAS DE ZAMORA (Journal of Industrial and Mechanical Engineering, 2019)
The current models of cities that are sought globally have generated the emergence of new concepts, one of which is distributed generation.This definition refers to the generation of electrical energy through the use of small sources of generation thatare located near the points of consumption.In turn, with it there is evidence of a cooperation between this microgeneration and the generation produced byconventional plants.This new form of generation makes use of renewable energy sources so it represents a great collaboration in terms of environmental care.For this reason, in the Engineering Faculty of Universidad Nacional de Lomas de Zamora (FI - UNLZ), a project has been carried out that places it as a generator and distributor of energy based on the use of solar energy to fulfill this purpose.
Keywords: distributed generation; renewable energies; microgeneration